Cohabitation and In Vitro Fertilization - Rodríguez Iturri, Roger (1985)
This article addresses two topics relevant to family law: cohabitation and in vitro fertilization. First, it analyzes concubinage as an ancient social practice resistant to eradication, even in the face of the influence of the Church. Although regulated in certain contexts, it continues to be a widespread phenomenon in several regions of Peru, where it adopts different names and forms. Second, in vitro fertilization, a recent scientific technique that has generated profound moral and legal dilemmas, is examined. In this line, the author highlights how this practice, initially developed in animals, currently raises challenges about filiation and parental rights in complex cases such as frozen embryos or insemination with external donors. In addition, the article highlights the need for law and morality to adapt to these new realities, especially with regard to the regulation of the family and the protection of human life. Finally, it stresses the importance of the State, in conjunction with experts, acting proactively to integrate these social and scientific realities into the legal framework, promoting legislation that respects both traditional customs and the advances of science.